2023
DOI: 10.1021/acsanm.3c01270
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Multimodal Sensors Based on Fibrous Porous Networks of Multiwalled Carbon Nanotubes and Polydimethylsiloxane for Sensing and Distinguishing Vertical and Shear Force

Abstract: Wearable sensors are one of the key components in applications such as motion monitoring, smart medical care, and human-computer interaction systems. In the present work, we focus on the simultaneous improvements of flexible sensors in both performance and functionality. Here, with a porous fiber network of multi-walled carbon nanotubes (MWCNTs)−polydimethylsiloxane (PDMS) as an active layer, a flexible pressure sensor with ultra-high sensitivity and superior capability of identifying transverse shear force an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Here, carbon allotropes have shown better performances, among which the MWCNT sensor fabricated has delivered 84818.2 kPa À1 of sensitivity. 258 From these figures, it may be concluded that each material category has the potential to be applied to tactile sensors with interesting values of GF/sensitivity.…”
Section: Conducting Polymers and Hydrogelsmentioning
confidence: 97%
See 1 more Smart Citation
“…Here, carbon allotropes have shown better performances, among which the MWCNT sensor fabricated has delivered 84818.2 kPa À1 of sensitivity. 258 From these figures, it may be concluded that each material category has the potential to be applied to tactile sensors with interesting values of GF/sensitivity.…”
Section: Conducting Polymers and Hydrogelsmentioning
confidence: 97%
“…In both these figures, materials are categorized in the order of the discussion in the material selection section. On the x axis, four sections are shown for metallic materials, 63,64,196,210,211,215,[250][251][252] carbon allotrope, 26,66,149,152,221,222,[252][253][254][255][256][257][258] conductive polymer and hydrogel, 153,237,240,[259][260][261] and composite of materials. 178,224,239,[262][263][264] The discussed articles are arranged in ascending order of the GF/sensitivity, whereas the y-axis shows the actual value.…”
Section: Conducting Polymers and Hydrogelsmentioning
confidence: 99%
“…Recently, flexible multimodal sensors responsive to multiple stimuli (humidity, temperature, etc.) in addition to mechanical stimuli are increasingly being investigated. However, most of the flexible devices are still based on nondegradable polymer materials. E-waste has enormous environmental pollution risks similar to traditional polymer materials and e-waste pollution of conventional inorganic electronic devices. Therefore, the development of green flexible devices utilizing degradable materials has been an urgent subject.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible sensors based on elastomeric polymers have gained significant interest across a range of fields such as robotics [ 1 , 2 ], healthcare [ 3 , 4 ], traffic monitoring [ 5 ], human motion detection [ 6 , 7 ], and intelligent tire technology [ 8 , 9 , 10 ] owing to their exceptional flexibility and ductility. Flexible capacitive pressure sensors stand out due to their stability and low power consumption [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%